2022
DOI: 10.1080/14786419.2022.2053852
|View full text |Cite
|
Sign up to set email alerts
|

A rare isoflavone-quinone and a new flavanone from the roots of Dalbergia stipulacea Roxb.

Abstract: Two previously undescribed compounds, namely dalpulapans F and G (1 and 2), along with 11 known compounds were isolated from the MeOH crude extract of the roots of Dalbergia stipulacea. Dalpulapan F was found as a rare isoflavone-quinone derivative. Their structures and absolute configurations were supported by extensive spectroscopic data analysis, including 1D and 2D NMR, HRESIMS data, specific rotation data, and comparison of the experimental and calculated ECD data. Cytotoxicity evaluation of the isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 9 (−)-12α-hydroxyrotenone from the methanol extract of D. stipulacea roots displayed cytotoxicity against HepG2 cell line with an IC 50 value of 18.01 ± 1.51 mM. 10 It was found that (−)-vestitol from the stems of this plant displayed the strongest antifungal activity against Pythium insidiosum and had higher activity than the amphotericin-B standard. 11 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“… 9 (−)-12α-hydroxyrotenone from the methanol extract of D. stipulacea roots displayed cytotoxicity against HepG2 cell line with an IC 50 value of 18.01 ± 1.51 mM. 10 It was found that (−)-vestitol from the stems of this plant displayed the strongest antifungal activity against Pythium insidiosum and had higher activity than the amphotericin-B standard. 11 …”
Section: Introductionmentioning
confidence: 98%
“…8 The chemical constituents from the stems and the roots of this plant are chalcones, isoflavonoids, flavonoids, pterocarpans, diterpenes and coumarins. 9–11 R , R -Velucarpin A, a pterocarpan, from the roots of this plant showed cytotoxicity against HeLa cells with an IC 50 value of 10.9 ± 0.42 μM (Posri et al , 2021). 9 (−)-12α-hydroxyrotenone from the methanol extract of D. stipulacea roots displayed cytotoxicity against HepG2 cell line with an IC 50 value of 18.01 ± 1.51 mM.…”
Section: Introductionmentioning
confidence: 99%